(untitled) (Geographical Journal of Nepal, 2022)
The intent of this study is to identify the impact of distance on the educational achievement of students at community schools in Dhankuta district of Province 1. Regarding the philosophical standpoint, this study embraces the positivist paradigm. The ontological assumption is the multiple realities of the phenomena. Similarly, the interaction and experiences of the participants are considered as epistemological understanding. Class eight students’ mark sheet (Mathematics, English, and Nepali) were studied to generate the quantitative data followed by a semi structured interview of purposively selected participants to generate the qualitative data. In the quantitative analysis, the mean and variance of distance and achievement were measured. Likewise, the Pearson’s correlation coefficient between distance and score in English, Mathematics, and Nepali were obtained by using the statistical software SPSS. In the qualitative phase, the phenomenological inquiry sought two essential themes related to distance from home and educational achievement, named subject preference and home school coordination. The quantitative and qualitative findings from the two phases of study proved that the travel distance of the student affects educational achievement, preferably in major subjects. Implications are provided for policy makers, concerned government institutions, and teachers to consider in countries’ educational reform.